Non-financial goals of municipal Social Housing Associations in managing the communal housing system - Dziadkiewicz, Michał (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Social rental housing is an important sector of the housing system aimed at meeting the housing needs of people whose economic strength does not allow them to purchase or rent real estate on the free market, and who at the same time do not qualify for social assistance in the form of the right to rent a municipal flat. In Poland, Social Housing Associations (hereinafter: SHAs; abbreviated and known in Poland as TBS) are the institutional form of this construction industry. SHAs, which are established by municipalities, play an important role in shaping the housing policy thanks to institutional possibilities allowing for the construction and renting of apartments, real estate management on the basis of commission contracts, or acting as a substitute investor. Aim: The aim of the article is to analyse the assumptions of the activities of municipal SHAs. As part of the research, the types of non-financial aims in the provisions of company agreements were examined, in particular according to the criterion of their going beyond the “pure” activity of SHAs, which is the construction and operation of apartments on the basis of lease. The article identifies the optimal selection of non-financial goals covering the areas of managing the housing stock and green areas in its vicinity and managing housing communities. Results: Thanks to the analysis of the provisions of the companies’ agreements of 62 municipal SHAs, it was found that the vast majority of them had non-financial goals that allow for complementary activities in the implementation of the municipal policy. The author managed to distinguish groups of provisions that could serve the implementation of the municipal policy in the field of housing, public property management, spatial order and greenery management.